• 2022-05-27
    当\( x < 0 \)时,函数曲线\( y = {x \over { { x^2} - 1}} \)的凹凸区间为( ) 。
    A: 在\( ( - \infty , - 1) \)内为凸,\( ( - 1,0) \)内为凹
    B: 在\( ( - \infty ,0) \)内为凸
    C: 在\( ( - \infty , - 1) \)内为凹,\( ( - 1,0) \)内为凸
    D: 在\( ( - \infty ,0) \)内为凹
  • A

    举一反三

    内容

    • 0

      函数$$y={{x}^{\frac{1}{x}}}\ \ (x&gt;0)$$的单调递增区间为(). A: $$(\text{e},+\infty )$$ B: $$(0,\ \text{e})$$ C: $$(1,+\infty )$$ D: $$(0,\ 1)$$

    • 1

      将\(f(x) = {1 \over {1 + {x^2}}}\)展开成\(x\)的幂级数为( )。 A: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} &amp; {} \cr } ( - \infty &lt; x &lt; + \infty )\) B: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} &amp; {} \cr } ( - 1&lt; x &lt; 1)\) C: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { {( - 1)}^n}{x^{2n}}} \matrix{ {} &amp; {} \cr } ( - 1 &lt; x &lt; 1)\) D: \({1 \over {1 + {x^2}}} = \sum\limits_{n = 0}^\infty { { x^{2n}}} \matrix{ {} &amp; {} \cr } ( - 1 &lt; x &lt; 1)\)

    • 2

      函数$f(x) = 2x^3-3x^2$的单调递减区间为 A: $[0,1]$ B: $[-\infty,0] \cup [1,\infty] $ C: $[-1,1]$ D: $[-\infty,-1] \cup [1,\infty]$

    • 3

      将\(f(x)=e^x\)展开成\((x-3)\)的幂级数为( )。 A: \(\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} &amp; {} \cr } ( - 1, 1)\) B: \({e^3}\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} &amp; {} \cr } ( - 1, 1)\) C: \(\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} &amp; {} \cr } ( - \infty , + \infty )\) D: \({e^3}\sum\limits_{n = 0}^\infty { { { { {(x - 3)}^n}} \over {n!}}} \matrix{ {} &amp; {} \cr } ( - \infty , + \infty )\)

    • 4

      将\(f(x) = {1 \over {2 - x}}\)展开成\(x \)的幂级数为( )。 A: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n }}}}} \),\(( - 2,2)\) B: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n }}}}} \),\(\left( { - 2,2} \right]\) C: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n + 1}}}}} \),\(( - 2,2)\) D: \({1 \over {2 - x}} = \sum\limits_{n = 0}^\infty { { { { x^n}} \over { { 2^{n + 1}}}}} \),\(\left( { - 2,2} \right]\)